Inflammatory bowel disease in twins : studies of genetics and environmental factors - Halfvarson, Jonas (Linköpings universitet, Faculty of Health Sciences, 2005)
A dissertation abstract. The dissertation focuses on the influence of genetics and environmental factors on inflammatory bowel disease in twins.
Linköping University medical dissertations, ISSN 0345-0082 No. 909
Keywords: Inflammatory Bowel Diseases; životní prostředí; gastroenterologie; rizikové faktory; Environment; Risk Factors; Genetic Predisposition to Disease; genetická predispozice k nemoci; nemoci u dvojčat; Diseases in Twins; idiopatické střevní záněty